Odpowiedź :
Odpowiedź:
Wyjaśnienie:
Cu + HNO₃st = Cu(NO₃)₂ + NO₂ + H₂O
Cu⁰ = Cu²⁺ + 2e utlenianie
N⁵⁺ +1e = N⁴⁺ |*2 redukcja
Cu⁰ = Cu²⁺ + 2e
2N⁵⁺ + 2e = 2N⁴⁺
Cu + 4HNO₃st = Cu(NO₃)₂ + 2NO₂ + 2H₂O
Cu reduktor
HNO₃ utleniacz
Cu + HNO₃roz = Cu(NO₃)₂ + NO + H₂O
Cu⁰ = Cu²⁺ + 2e |*3 utlenianie
N⁵⁺ + 3e = N²⁺ |*2 redukcja
3Cu⁰ = 3Cu²⁺ +6e
2N⁵⁺ + 6e = 2N²⁺
3Cu + 8HNO₃roz = 3Cu(NO₃)₂ + 2NO + 4H₂O
Cu reduktor
HNO₃ utleniacz
Al + H₂SO₄roz = Al₂(SO₄)₃ + H₂
Al⁰ = Al³⁺ + 3e |*2 utlenianie
2H¹⁺ + 2e= H₂⁰ |*3 redukcja
2Al⁰ = 2Al³⁺ + 6e
6H¹⁺ + 6e = 3H₂⁰
2Al + 3H₂SO₄roz = Al₂(SO₄)₃ + 3H₂
Al reduktor
H₂SO₄ utleniacz